Supplementary Table S1 from Validation of the Clinical Use of GIScar, an Academic-developed Genomic Instability Score Predicting Sensitivity to Maintenance Olaparib for Ovarian Cancer - Raphaël Leman (17314506) (2025)
prospective collection used to train GIScar (n = 250)